Long-term social isolation stress exacerbates sex-specific neurodegeneration markers in a natural model of Alzheimer’s disease - Oliva, Carolina A.; Lira, Matías; Jara, Claudia; Catenaccio, Alejandra; Mariqueo, Trinidad A.; Lindsay, Carolina B.; Bozinovic, Francisco; Cavieres, Grisel; Inestrosa, Nibaldo C.; Tapia-Rojas, Cheril; Rivera, Daniela S. (Frontiers in Aging Neuroscience, 2023)
Social interactions have a significant impact on health in humans and animal models. Social isolation initiates a cascade of stress-related physiological disorders and stands as a significant risk factor for a wide spectrum of morbidity and mortality. Indeed, social isolation stress (SIS) is indicative of cognitive decline and risk to neurodegenerative conditions, including Alzheimer’s disease (AD). This study aimed to evaluate the impact of chronic, long-term SIS on the propensity to develop hallmarks of AD in young degus (Octodon degus), a long-lived animal model that mimics sporadic AD naturally. We examined inflammatory factors, bioenergetic status, reactive oxygen species (ROS), oxidative stress, antioxidants, abnormal proteins, tau protein, and amyloid-β (Aβ) levels in the hippocampus of female and male degus that were socially isolated from post-natal and post-weaning until adulthood. Additionally, we explored the effect of resocialization following chronic isolation on these protein profiles. Our results showed that SIS promotes a pro-inflammatory scenario more severe in males, a response that was partially mitigated by a period of resocialization. In addition, ATP levels, ROS, and markers of oxidative stress are severely affected in female degus, where a period of resocialization fails to restore them as it does in males. In females, these effects might be linked to antioxidant enzymes like catalase, which experience a decline across all SIS treatments without recovery during resocialization. Although in males, a previous enzyme in the antioxidant pathway diminishes in all treatments, catalase rebounds during resocialization. Notably, males have less mature neurons after chronic isolation, whereas phosphorylated tau and all detectable forms of Aβ increased in both sexes, persisting even post-resocialization. Collectively, these findings suggest that long-term SIS may render males more susceptible to inflammatory states, while females are predisposed to oxidative states. In both scenarios, the accumulation of tau and Aβ proteins increases the individual susceptibility to early-onset neurodegenerative conditions such as AD.